Analysis of the Maintenance of Operational Facilities for the PKP-PK Unit in Supporting Aviation Safety at Iskandar Pangkalan Bun Airport - Nanda Alief Segara Pangestu; Kartika Fajar Nieamah (CV. Rayyan Dwi Bharata, 2023)
Care and maintenance of PKP-PK operational vehicle facilities, one of the things that must be done by personnel to provide accident services in the airport area, is the same as at Iskandar Pangkalan Bun airport for the care and maintenance of main and supporting vehicles in accordance with the Regulations of the Directorate of Civil Aviation KP.14 of 2015. The purpose of this study was to find out qualitatively about the components that must be considered every day in maintaining operational vehicles at Iskandar Pangkalan Bun Airport. The research design is a qualitative study in the form of a case study using observation sheets and in-depth interviews with PKP-PK personnel and PKP-PK units at Iskandar Pangkalan Bun Airport. The results of the study indicate that the obstacles experienced by PKP-PK personnel in carrying out maintenance and maintenance of operational vehicles, namely the procurement of vehicle parts, in which the PKP-PK unit at Iskandar Airport has various car brands (manufacturing factories).